Bacteriostasis evaluation of the different soaking solutions in perineal skin preparation before the male urethral open operation: a randomized controlled trial. Issue 2 (14th October 2014) - Ma, Li; Liu, Ling; Tian, Ye; Peng, Yinqiong; Wang, Kunjie; Wu, Tao; Liu, Changqing
ABSTRACT Perineal soaking is of crucial importance for skin preparation before the male urethral open operation; however, soaking solutions vary across the world. The aim of this research was to explore the bacteriostasis efficacy of the different soaking solutions in perineal skin preparation before the operation. Thirty‐six patients were randomly divided into three groups. In Group A, 0·1% povidone iodine was used to soak the 12 patients' perineum to reduce the bacterial load of the skin preparation before the operation. Similarly, combination of 0·1% povidone iodine and 1·6% saline for Group B and 1·6% saline for Group C was used. Bacteria samples were collected in four sites of the patients' perineum, before soaking, 1 d after soaking and 2 d after soaking, respectively. No serious adverse reactions were observed. There was a significant lower bacteria load in Group C after soaking (P = 0·032). For penoscrotal junction, there were significant lower bacteria loads after soaking in both Group A and Group B compared with Group C (P = 0·009), and there was significant lower bacteria load after soaking in Group A (P = 0·001) and Group B (P = 0·017). Similar with penoscrotal junction, bacteria load at the bottom of the scrotum decreased significantly in Group A (P = 0·001) and Group B (P = 0·002) and there were significant lower bacteria loads after soaking in both Group A and Group B compared with Group C (P = 0·041). In the middle of the penis, still, there were significant lower bacteria loads after soaking in both Group A and Group B compared with Group C (P = 0·019), and there was significant lower bacteria load after soaking in Group A (P = 0·012) and Group B (P = 0·006). In conclusion, combination of 0·1% povidone iodine and 1·6% saline solution for the preoperative skin preparation of male open urethral operation is safe and efficient.